Water Absorption and Release Characteristics of a Polymer and its Effect on Available Water Content, Tomato (Lycopersicon esculentum) Productivity and Water Use Efficiency in a Semi-arid Sandy Loam Soil - K. Srinivas Reddy, Minakshi T. Grover, B. Srinivas; B. Venkateswarlu, K. Sammi Reddy, K. Srinivas, A.G.K. Reddy, K.L. Sharma, A.K. Indoria (Journal of the Indian Society of Soil Science, 2016)
The problem of inefficient use of rain and irrigation water by crops is most important on light textured soils of semi-arid and arid regions. Application of super absorbent polymers into the soil could be one of the effective ways to increase water use efficiency in crops. Therefore, laboratory and field investigations have been conducted to study water retention and release characteristics of a cross linked polymer of polyacrylamide and potassium acrylate (PAM) and to evaluate its effect on yield and water productivity in tomato grown on sandy loam soil under field conditions. In laboratory studies, irrespective of source of water, polymer showed rapid initial hydration followed by no more water absorption towards the point of equilibrium. Overall, the amount of water absorbed by one gram of polymer ranged from 247-369 g in distilled water, 141-175 g in 50% Hoagland solution, 120-155 g in irrigation water, 116-141 g in 100% Hoagland solution, 96-115 g in 0.01 M CaCl2 and 86-111 g in 200% Hoagland solution over 5 – 240 min saturation period. The amount of water absorbed by polymer decreased from 360 to 110 g g-1 with increasing electrical conductivity (EC) of the source of water from 0.03 to 2.23 dS m-1. Application of polymer at graded rates (0.25-1.0% of soil, w/w) to sandy loam and sandy clay loam soils increased the available water content by 101-192 per cent as compared to untreated soils. In field experiment, at every week irrigation, application of polymer @ 25 or 50 kg ha-1 had no significant effect on tomato plant height and fruit yield. Similarly, application of polymer had no significant effect on plant height and fruit yield when tomato was irrigated every third week. But application of polymer at 25 kg ha-1 with alternate week irrigation not only produced the higher tomato yield but also increased the water productivity to 290.6 kg ha-mm-1 and thereby saved 180 ha-mm irrigation waters during a crop growth season.